Preventing depression in the community by voluntary sector providers (PERSUADE): intervention development and protocol for a parallel randomised controlled feasibility trial - Pim Cuijpers; Waquas Waheed; Peter Bower; Amy Blakemore; Cassandra Kenning; Melina Safari; June SL Brown; Mark Hann; Nicky Lidbetter; Ricardo F Muñoz (BMJ Open)
Introduction Depression is now the most common illness worldwide affecting more than 300 million people. Studies modelling the impact of depression interventions have shown that the burden of depression cannot be minimised by more than 35% with existing treatments. There is a need to develop better preventative interventions. The overall aim of this programme of work is to develop interventions to reduce depression symptom scores and prevent development of depression in people with subthreshold depression. The objectives are to adapt a low intensity community-based depression prevention intervention, establish the acceptability and uptake of this model and conduct a parallel randomised controlled feasibility trial to inform a full-scale trial.Methods and analysis Focus groups will be run with members of the public, voluntary sector providers and researchers to inform the adaptation of an existing depression prevention course. Sixty-four people with subthreshold depression, as represented by a score of between 5 and 9 on the Patient Health Questionnaire-9 depression measure, will be recruited to take part in the feasibility trial. Participants will be randomised equally to the intervention or usual care control groups. Participants in the intervention group will receive the new revised manual and attend a 1-day workshop delivered by voluntary sector service providers. Outcome measures will be completed 3 months after baseline. Quantitative data on recruitment, randomisation, attendance, retention, questionnaire completion rates will be collected. Primary analyses will be descriptive and a process evaluation will be conducted to assess the processes involved in implementing the intervention. Interviews will be conducted to explore acceptability and framework analysis will be used to analyse the data.Ethics and dissemination The study has been reviewed and approved by NHS Research and Ethics Committee: NW-Greater Manchester East. The results will be actively disseminated through peer-reviewed journals, conference presentations, social media, the internet and community engagement activities.Trial registration number ISRCTN23278208;Pre-results.